Theological and Cultural Perspectives on Gender Identity in Igboland: Examining Biblical and Folk Evidence Against Transgenderism (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
This study explores the theological and cultural perspectives on gender identity in Igbo cosmology, emphasizing biblical and folk evidence against transgenderism. The study incorporates both personal communications with regal Igbo elders cum the consultation of extant literature apposite to its objective as the mode of data collection. The Theory of Transgender contradictions as projected by Anderson (2018) were leveraged in appraising this study. The necessary generalizations and conclusions were drawn purely on the qualitative analysis and synthesis of the gathered data made through phenomenological, hermeneutical and culture centered approaches. Observations indicate that in as much as transgender individuals operate in the closet in Igbo land, there are some Igbo natives both in diasporas and homeland that underwent medical or surgical transitions to live in accordance with their identified gender; whereas others simply settle for gender identity that does not align with their sex at birth including non-binary cum gender queer identities: They mostly express such via effeminate and butch dispositions. This study underscores that within the Christian structure, the bible which is a major Christian theological foundation affirms the immutable divine conception of gender as distinctly male and female in Genesis 1:27 and Deuteronomy 22:5. Hence any deviation from one’s biological sex is inconsistent with biblical teachings; and thus, an aberration, a revolution against God and fraud against humanity. Similarly, the Igbo cosmology and folklore accentuate the importance of maintaining societal harmony and spiritual balance through adherence to and celebration of the established gender sanctity at birth as male and female. The Igbo people thus perceives transgender and other associated learned behaviours as abomination. This study ultimately advocates that mankind should anchor on the truth as addressed in the bible regarding human sexuality. Humankind should equally eschew from transgenderism since it provokes curse upon people that conform to such as conceive in the Igbo culture. The Igbo cultural custodians and church leaders should always be firm in their teachings and injunctions on the sanctity of gender origin divinely ordained at birth.
Keywords: Gender Identity; Theological; Cultural; Biblical; Folk; Transgenderism; Perspectives